2000
DOI: 10.1016/s0925-4773(99)00311-1
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 is required for early heart development during a distinct time period

Abstract: BMP2, like its Drosophila homologue dpp, is an important signaling molecule for specification of cardiogenic mesoderm in vertebrates. Here, we analyzed the time-course of BMP2-requirement for early heart formation in whole chick embryos and in explants of antero-lateral plate mesoderm. Addition of Noggin to explants isolated at stage 4 and cultured for 24 h resulted in loss of NKX2.5, GATA4, eHAND, Mef2A and vMHC expression. At stages 5-8 the individual genes showed differential sensitivity to Noggin addition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 54 publications
7
160
1
5
Order By: Relevance
“…In situ hybridization data in the developing chick, frog, and/or mouse has shown that BMP2, BMP4, FGF4, FGF8, WNT11, Dkk1, and crescent are expressed at the right time and place to act as primary stimulators of heart formation in the developing embryo (Kispert et al, 1996;Schultheiss et al, 1997;Shibata et al, 2000;Niehrs et al, 2001;Alsan and Schultheiss, 2002). Moreover, specific inhibition of the expression and/or activity of WNT11 or BMP can significantly diminish the formation of cardiac tissue in the vertebrate embryo (Schultheiss et al, 1997;Schlange et al, 2000;Pandur et al, 2002).…”
Section: Specification Of Precardiac Mesoderm Cellsmentioning
confidence: 99%
“…In situ hybridization data in the developing chick, frog, and/or mouse has shown that BMP2, BMP4, FGF4, FGF8, WNT11, Dkk1, and crescent are expressed at the right time and place to act as primary stimulators of heart formation in the developing embryo (Kispert et al, 1996;Schultheiss et al, 1997;Shibata et al, 2000;Niehrs et al, 2001;Alsan and Schultheiss, 2002). Moreover, specific inhibition of the expression and/or activity of WNT11 or BMP can significantly diminish the formation of cardiac tissue in the vertebrate embryo (Schultheiss et al, 1997;Schlange et al, 2000;Pandur et al, 2002).…”
Section: Specification Of Precardiac Mesoderm Cellsmentioning
confidence: 99%
“…The BMP antagonist noggin blocks cardiogenesis in explants of stage 4 precardiac mesoendoderm and blocks cardiogenesis in vivo when ectopically expressed through stage 7 Schlange et al 2000). Conversely, anterior paraxial mesoderm, which lies medial to the heart-forming region and normally gives rise to head mesenchyme, can be induced to express cardiac genes and to form beating cardiac myocytes in explant culture by exposure to BMP-2 at stages 5-6 Andreé et al 1998).…”
mentioning
confidence: 99%
“…Conversely, anterior paraxial mesoderm, which lies medial to the heart-forming region and normally gives rise to head mesenchyme, can be induced to express cardiac genes and to form beating cardiac myocytes in explant culture by exposure to BMP-2 at stages 5-6 Andreé et al 1998). In vivo, implantation of a BMP-2-soaked bead into the anterior paraxial mesoderm induces the expression of Nkx-2.5 and GATA-4 Schlange et al 2000). While BMP signals can induce robust cardiac differentiation from an-terior gastrula stage mesendoderm, posterior mesoderm fails to activate heart markers in response to BMP signals .…”
mentioning
confidence: 99%
“…Members of the bone morphogenetic protein (BMP) family are expressed adjacent to the heart-forming region in avians, and ectopic expression of the BMP antagonist noggin in chick precardiac mesoderm inhibits cardiogenesis (Schultheiss et al 1997;Schlange et al 2000). Conversely, application of BMP2 or BMP4 to chick anterior mesoderm located medial to the heart forming region induces ectopic cardiogenesis (Schultheiss et al 1997;Andree et al 1998).…”
mentioning
confidence: 99%